PENGARUH PERMAINAN BOLA PANTUL TERHADAP KEMAMPUAN SERVIS ATAS BOLA VOLI PADA SISWA SMPN 2 NANGA PINOH - Rapi Turiansyah; Eko Rudiansyah; Suyatmin Suyatmin (STKIP Melawi, 2020)
Abstract: The purpose of this study was to determine effect of reflective ball media on the abilityto servis on volleyball game of state juniot high school students Nanga Pinoh. The design used inthe study was One Group Pretest-Posttest Design